ANALISIS DAMPAK KOREKSI FISKAL PENYUSUTAN ASET TETAP TERHADAP PAJAK PENGHASILAN BADAN PADA PT. ALAM SEGAR - Aryani, Farida; Romanda, Candra (Institut Rahmaniyah Sekayu, 2023)
This descriptive research is aimed to analyze the fiscal corrections impact for fixed asset depreciation on corporate income tax at PT.Alam Segar. The analysis technique is conducted by comparing calculation of fixed assets depreciation according to commercial accounting with fiscal accounting, also calculation of PT.Alam Segar Corporate Income Tax 2022. The secondary data analyzed is depreciation of fixed assets and income and operational costs. The research results show although the depreciation method used is the same, the results of the fixed asset depreciation calculations are different. Fixed assets depreciation according to commercial accounting is Rp.308,750,000 and fiscal accounting is Rp.265,425,000. There is a difference in depreciation charges of Rp.43,325,000. This difference causes need for a positive fiscal correction. This correction has an impact on the amount of profit as a basis for calculating tax from Rp.1,669,000,000 to Rp.1,712,325,000. There is a difference in the increase in the amount of PPh payable due to fiscal corrections amounting to Rp.9,531,500. PT.Alam Segar is expected to calculate Income Tax correctly and accurately. KPP is expected to conduct intensive socialization, therefore all taxpayers understand changes in applicable tax regulations.